Mitochondrial Carnitine/Acylcarnitine Translocase: Insights in Structure/ Function Relationships. Basis for Drug Therapy and Side Effects Prediction - Tonazzi, Annamaria; Giangregorio, Nicola; Console, Lara; Indiveri, Cesare (Mini Reviews in Medicinal Chemistry, 2015)
The mitochondrial carnitine/acylcarnitine translocase has been identified, purified and reconstituted in liposomes in 1990. Since that time it has been object of studies aimed to characterize its function and to define the molecular determinants of the translocation pathway. Thanks to these tenacious studies the molecular map of the amino acids involved in the catalysis has been constructed and the roles of critical residues in the translocation pathway have been elucidated. This has been possible through the combination of transport assay in reconstituted liposomes, site-directed mutagenesis, chemical labeling and bioinformatics. Recently some molecules which modulate CACT activity have been identified, such as glutathione and hydrogen peroxide, constituting some of the few cases of control mechanisms of mitochondrial carriers. The vast knowledge on the carnitine/acylcarnitine translocase is essential both as a progress in basic science and as instrument to foresee therapeutic or toxic effects of xenobiotics and drugs. Such studies have been already started pointing out the inhibitory action of drugs such as K+/H+-ATPase inhibitors (omeprazole) or antibiotics (β-lactams) on the carnitine/acylcarnitine translocase, which can explain some of their adverse effects.
Keywords: mutagenesis